Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ijs.12290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Living and Socioeconomic Characteristics on Cardiovascular Risk in Ischemic Stroke Patients

Abstract: Vascular risk in stroke patients in low- and middle-income countries varies not only with the number of arterial beds involved but also with socioeconomic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…We found a positive association between stroke and lower level of education in the index study which was also is similar to the report by Amarenco et al [48] who observed that low level of education, unemployment status and low quality of living were predictive of major vascular events. People in low level of education are more likely to earn less and affected by factors discussed earlier.…”
Section: Discussionsupporting
confidence: 91%
“…We found a positive association between stroke and lower level of education in the index study which was also is similar to the report by Amarenco et al [48] who observed that low level of education, unemployment status and low quality of living were predictive of major vascular events. People in low level of education are more likely to earn less and affected by factors discussed earlier.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, regarding our previous OPTIC publication [10] showing an independent association of socioeconomics factors with cardiovascular risk, a multivariable model was performed by including socioeconomics factors as covariables. Thus, the following additional models were considered, which included model 1 variables plus hypertension, dyslipidemia, and smoking (model 2); model 2 variables plus body mass index and diabetes (model 3); and model 3 variables plus socioeconomic data (model 4).…”
Section: Methodsmentioning
confidence: 99%
“…The average hospitalization costs are high (2). Furthermore, the morbidity, disability and mortality of heart failure following myocardial infarction severely affects the quality of life of the patient and community health care resources.…”
Section: Introductionmentioning
confidence: 99%